One‐Dimensionally Disordered Chiral Sorting by Racemic Tiling in a Surface‐Confined Supramolecular Assembly of Achiral Tectons. Issue 27 (7th June 2017) - Zhang, Yi‐Qi; Lin, Tao; Cirera, Borja; Hellwig, Raphael; Palma, Carlos‐Andres; Chen, Zhi; Ruben, Mario; Barth, Johannes V.; Klappenberger, Florian
Abstract: The aggregation of (pro)chiral/achiral molecules into crystalline structures at interfaces forms conglomerates, racemates, and solid solutions, comparable to known bulk phases. Scanning tunneling microscopy and Monte Carlo simulations were employed to uncover a distinct racemic phase, expressing 1D disordered chiral sorting through random tiling in surface‐confined supramolecularly assembled achiral 4, 4′′‐diethynyl‐1, 1′:4′, 1′′‐terphenyl molecules. The configurational entropy of the 1D disordered racemic tiling phase was verified by analytical modeling, and found to lie between that of a perfectly ordered 2D racemate and a racemic solid solution. Abstract : Clash of the tectons : Scanning tunneling microscopy and Monte Carlo simulations supported by analytical modeling were used to visualize a distinct racemic phase in surface‐confined supramolecularly assembled achiral tectons. The racemic phase expressed 1D disordered chiral sorting by random tiling.